Extended Perineural Analgesia After Hip and Knee Replacement When Buprenorphine-Clonidine-Dexamethasone Is Added to Bupivacaine: Preliminary Report from a Randomized Clinical Trial. Issue 11 (7th October 2020) - Williams, Brian A; Ibinson, James W; Ritter, Marsha E; Ezaru, Catalin S; Rakesh, Hulimangala R; Paiste, Henry J; Gilbert, Karen L; Mikolic, Joseph M; Muluk, Visala S; Piva, Sara R
Abstract: Objective: We tested the hypothesis that buprenorphine-clonidine-dexamethasone (BCD) extends perineural analgesia compared with plain bupivacaine (BPV) nerve blocks used for hip and knee replacement surgery. Design: Prospective, parallel-arms, randomized, double-blind trial. Setting: A single veterans' hospital. Subjects: Seventy-eight veterans scheduled for total hip or knee replacement with plans for spinal as the primary anesthetic. Methods: Participants underwent nerve/plexus blocks at L2–L4 and L4–S3 in advance of hip or knee joint replacement surgery. Patients were randomized to receive BPV-BCD or plain BPV in a 4:1 allocation ratio. Patients answered four block duration questions (listed below). Time differences between treatments were analyzed using the t test. Results: Significant ( P < 0.001) prolongation of the time parameters was reported by patients after the BPV-BCD blocks (N = 62) vs plain BPV (N = 16). The time until start of postoperative pain was 26 vs 11 hours (mean difference = 15 hours, 95% CI = 8 to 21). The time until no pain relief from the blocks was 32 vs 15 hours (mean difference = 17 hours, 95% CI = 10 to 24). The time until the numbness wore off was 37 vs 21 hours (mean difference = 16 hours, 95% CI = 8 to 23). The time until the worst postoperative pain was 39 vs 20 hours (mean difference = 19 hours, 95% CI = 11 to 27). Conclusions: BPV-BCD provided 26–39 hours of perineural analgesia in the L2–L4 and L4–S3 nerve distributions after hip/knee replacement surgery, compared with 11–21 hours for plain BPV.